2022
DOI: 10.1542/peds.2022-056230
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Incidence Among Sixth Through Twelfth Grade Students by Vaccination Status

Abstract: Coronavirus disease 2019 (COVID-19), school closures, and quarantines have had substantial impacts on students’ health and education.1,2,3 Clinical trials have shown severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccines to be safe and efficacious for adults, adolescents, and young children.4 However, in some areas, vaccine uptake has been low among children and adolescents, especially compared to uptake in adults.1 Additionally, real-world vaccine effectiveness data among adolescents and implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…1,2 The BNT162b2 vaccine (Pfizer/BioNTech) is recommended as a 2-dose primary series with a third dose administered at least 5 months after the second dose for adolescents aged 12 to 17 years of age in the US. 3 Limited data describing vaccine effectiveness (VE) of BNT162b2 in this age group are available, [4][5][6][7][8][9][10][11] and to our knowledge, only 2 preprint reports 11,12 and 2 published reports 13,14 have estimated VE against Omicron. Both preprint reports 11,12 evaluated VE primarily against infection or symptomatic COVID-19 only.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The BNT162b2 vaccine (Pfizer/BioNTech) is recommended as a 2-dose primary series with a third dose administered at least 5 months after the second dose for adolescents aged 12 to 17 years of age in the US. 3 Limited data describing vaccine effectiveness (VE) of BNT162b2 in this age group are available, [4][5][6][7][8][9][10][11] and to our knowledge, only 2 preprint reports 11,12 and 2 published reports 13,14 have estimated VE against Omicron. Both preprint reports 11,12 evaluated VE primarily against infection or symptomatic COVID-19 only.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it was determined that 79.9% of the participants were vaccinated against Covid-19. Thakkar et al has reported that 829 (73.5%) students were vaccinated in their study conducted with 1128 students in the South Carolina region 20 . The frequency of those in the 0-19 age group who received at least one dose of vaccine was 62.95% in Hong Kong and 45.7% in Italy 21 .…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent transmission studies from large exposures or household studies have shown that children are as likely to become infected as adults and are able to transmit the virus to others [5,6]. However, with appropriate precautions, COVID-19 transmission from children, such as in in-person school settings, has been rare, particularly amongst vaccinated students [7][8][9][10].…”
Section: Covid-19 Infections In Childrenmentioning
confidence: 99%